2021
DOI: 10.3389/fphar.2021.659627
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nervilia fordii Extract on Pulmonary Fibrosis Through TGF-β/Smad Signaling Pathway

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive and irreversible interstitial pulmonary disease with a poor prognosis. The extract of Nervilia fordii (NFE) has shown remarkable benefit in the treatment of acute lung injury, lung cancer, and severe acute respiratory syndrome (SARS). However, the potential mechanism and efficacy of NFE in the treatment of IPF remain unknown. In this study, a systematic network pharmacology analysis was used to predict the mechanism and efficacy of NFE in the treatment of IP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Quercetin has a variety of biological properties, such as antioxidant, anti-inflammatory, and antiapoptosis [22][23][24], which has been widely investigated in human cancers, including lung cancer. It was reported that the antiproliferative [27]. e antitumor effects of rhamnazin were also proved in hepatocellular carcinoma [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin has a variety of biological properties, such as antioxidant, anti-inflammatory, and antiapoptosis [22][23][24], which has been widely investigated in human cancers, including lung cancer. It was reported that the antiproliferative [27]. e antitumor effects of rhamnazin were also proved in hepatocellular carcinoma [28].…”
Section: Discussionmentioning
confidence: 99%
“…The antitumor functions of the other three bioactive compounds are also found in documented reports of lung cancer or other cancers. Yao et al demonstrated that rhamnazin may exert a therapeutic effect on pulmonary fibrosis by alleviating inflammation, oxidation, and collagen deposition via the TGF- β /Smad axis [ 27 ]. The antitumor effects of rhamnazin were also proved in hepatocellular carcinoma [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The key mechanism of SSc-ILD pathogenesis is persistent lung damage caused by alveoli macrophage activation, which induces the release of a variety of profibrosis cytokines, prompts the conversion of pulmonary epithelial cells to interstitial cells (EMT), and eventually results in the formation of pulmonary fibrosis [ 21 ]. Recently, TCM has been more and more accepted in the treatment of pulmonary fibrosis worldwide [ 22 ]; Yangyin Yiqi Mixture [ 23 ], Nervilia fordii extract [ 24 ], and Inulae Flos [ 25 ] have a good effect on pulmonary fibrosis with few side effects. Although the active role of PESV on SSc-ILD is unclear, a published study has proved that PESV obviously improves fibrosis in rats with doxorubicin-induced acute cardiotoxicity [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…is a small, terrestrial, and short-lived perennial plant (Orchidaceae) that is endemic to the karst limestone mountains ( Figures 1A–D ) in Guangxi Province, China. The whole plant or the aerial part of N. fordii ( Figure 1E ) are used as premium dishes, herbal tea, and folk medicine ( Qiu et al, 2013 ) because of their excellent pharmacological capacities, such as antimicrobial ( Li et al, 2017 ; Xu et al, 2017 ), anticancer ( Yao et al, 2021 ), antiviral ( Tian et al, 2009 ), and anti-inflammatory ( Yin et al, 2021 ) effects. In particular, this plant was widely used as a main ingredient in traditional Chinese medicine formulations to treat patients with severe acute respiratory syndrome in 2013 ( Qiu et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%